2017
DOI: 10.4140/tcp.n.2017.728
|View full text |Cite
|
Sign up to set email alerts
|

Medication Refusal: Resident Rights, Administration Dilemma

Abstract: Occasionally, residents actively or passively refuse to take medications. Residents may refuse medication for a number of reasons, including religious beliefs, dietary restrictions, misunderstandings, cognitive impairment, desire to self-harm, or simple inconvenience. This action creates a unique situation for pharmacists and long-term facility staff, especially if patients have dementia. Residents have the legal right to refuse medications, and long-term care facilities need to employ a process to resolve dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…At a broader level, the idea of refusal of/resistance to a care act of some kind – and the way in which staff respond to this challenge – is well documented in the dementia care literature. There are examples in the context of medication ( Haskins & Wick, 2017 ; Young & Unger, 2016 ), oral hygiene ( Jablonski, et al, 2011 ) and general care ( Konno, et al, 2012 ; Mahoney et al, 1999 ). It is not clear why there is a relative absence of this theme in mealtime care literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At a broader level, the idea of refusal of/resistance to a care act of some kind – and the way in which staff respond to this challenge – is well documented in the dementia care literature. There are examples in the context of medication ( Haskins & Wick, 2017 ; Young & Unger, 2016 ), oral hygiene ( Jablonski, et al, 2011 ) and general care ( Konno, et al, 2012 ; Mahoney et al, 1999 ). It is not clear why there is a relative absence of this theme in mealtime care literature.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples in the context of medication (Haskins & Wick, 2017;Young & Unger, 2016), oral hygiene (Jablonski, et al, 2011) and general care (Konno, et al, 2012;Mahoney et al, 1999). It is not clear why there is a relative absence of this theme in mealtime care literature.…”
Section: Comparison To Other Literaturementioning
confidence: 99%
“…This may be explained by the fact that the publicity of disease prevention mainly focuses on lifestyle elements [31,32], thus neglecting the fact that chronic diseases, including hypertension and diabetes, are risk factors for dementia [17]. Moreover, medication refusal is common in the general population [33], and people are often more concerned about the side effects of antihypertensive and hypolipidemic drugs than their beneficial effects [34]. Other studies also found that people had less knowledge about the role of cardiovascular disease management in the development of dementia [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…43 If it is not resolved by the healthcare team, an ethical dilemma may occur given its impact on the patient's care outcome. 65 As if it is not a perfect solution, the use of clinical guidelines and a three-step approach of the physician, ethics committee, and guardian have been suggested. 64 The essential legislative core for all European member states to guarantee the protection of human rights regarding biology, medicine and healthcare is the ‘Convention for the Protection of Human Rights and Dignity of the Human Being about the Application of Biology and Medicine’ 66 and its additional protocol.…”
Section: Ethics Of Administration Of Prn Medications To Incapacitated Patientsmentioning
confidence: 99%